The Utilization of Virtual Laboratory in Learning: A Meta-Analysis - Zaturrahmi, Zaturrahmi; Festiyed, Festiyed; Ellizar, Ellizar (Indonesian Journal of Science and Mathematics Education, 2020)
This study aimed to analyze the use of technology in the form of virtual laboratories in learning, including: (1) problems that cause the use of virtual laboratories in learning, (2) variables that are influenced by the use of virtual laboratories in learning, and (3) Scientific fields that utilize virtual laboratories in learning. The research method used was a meta-analysis with a sample of 30 international journal articles. Data collection was done by collecting similar scientific articles related to virtual laboratories and then analyzing them. The results of this meta-analysis study indicate that the main problem that causes the use of virtual laboratories in learning is the low understanding of students' concepts of learning topics. Furthermore, the variable most affected by the use of virtual laboratories is student achievement. Finally, the scientific field that most often utilizes virtual laboratories in learning is Physics.